2022
DOI: 10.1111/ssqu.13147
|View full text |Cite
|
Sign up to set email alerts
|

Trust in physicians and trust in government predict COVID‐19 vaccine uptake

Abstract: We consider how trust in government, trust in physicians, and interpersonal trust affect the likelihood of COVID-19 vaccine uptake. Methods: A survey of 3057 registered South Dakota voters was fielded in April 2021 that measured COVID-19 vaccine uptake, three aspects of trust, and several other factors related to vaccine hesitancy. Logistic regression was utilized to analyze the responses. Results: We found positive, statistically significant, and substantively impactful effects for trust in government and tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 57 publications
(104 reference statements)
4
23
0
Order By: Relevance
“…Conversely, the lowest nutrition-health misinformation scores were found in respondents who more frequently relied on advice from their own medical doctors, nutrition scientists, PhDs and academics, and nutrition professionals for making dietary changes. This corresponds with other research that highlights that higher trust in medical and health professionals and scientists is associated with a lower susceptibility to COVID-19 misinformation [ 136 , 147 , 148 , 149 ].…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, the lowest nutrition-health misinformation scores were found in respondents who more frequently relied on advice from their own medical doctors, nutrition scientists, PhDs and academics, and nutrition professionals for making dietary changes. This corresponds with other research that highlights that higher trust in medical and health professionals and scientists is associated with a lower susceptibility to COVID-19 misinformation [ 136 , 147 , 148 , 149 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our results also show the importance of trust in government as a predictor of attitudes towards COVID-19 vaccine mandates. Scholars showed that trust in government is a strong predictor of vaccination attitudes and vaccination status ( Jennings et al, 2021 ; Viskupic et al., 2022 ). It is unsurprising that those individuals with high trust in the government are more likely to support a vaccine mandate, which they consider appropriate and necessary in bringing the pandemic under control.…”
Section: Discussionmentioning
confidence: 99%
“…Trust in government and partisan self-identification are the independent variables of primary interest. Several control variables that have been found to shape attitudes on COVID-19 mitigation were also included: evangelical identity, partisan self-identification, age, gender, education, and COVID-19 vaccination status ( Adams et al, 2021 ; Corcoran et al, 2021 ; DeMora et al, 2021 ; Myerson et al, 2021 ; Viskupic et al, 2022 ). The survey also included an attention check question, which 98.3% participants answered correctly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, those with greater trust in the government were more likely to adhere to preventive measures (Gotanda et al, 2021). Both trust in the government and trust in physicians were positively related to COVID-19 vaccine uptake (Viskupič et al, 2022). However, individuals with strong trust in politicians exhibited low personal compliance.…”
Section: Literature Review Covid-and Trust In Government Science and ...mentioning
confidence: 99%